2018
DOI: 10.1136/oemed-2017-104865
|View full text |Cite
|
Sign up to set email alerts
|

Dual impact of organisational change on subsequent exit from work unit and sickness absence: a longitudinal study among public healthcare employees

Abstract: ObjectivesWe investigated work-unit exit, total and long-term sickness absence following organisational change among public healthcare employees.MethodsThe study population comprised employees from the Capital Region of Denmark (n=14 388). Data on reorganisation at the work-unit level (merger, demerger, relocation, change of management, employee layoff or budget cut) between July and December 2013 were obtained via surveys distributed to the managers of each work unit. Individual-level data on work-unit exit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
4
12
1
1
Order By: Relevance
“…The results of this study show a significantly reduced risk of short-term sickness absence prior to unit-level downsizing and a significantly increased risk of short-term sickness absence after unit-level downsizing. Similar to our previous study [ 16 ], the results only partially corroborate prior research showing a relationship between organizational change and increased sickness absence and reduced health [ 2 , 57 ], also at the unit-level [ 8 10 ]. Indeed, in line with Østhus and Mastekaasa [ 12 ], our results did not show increased long-term sickness absence at any stage of the downsizing process.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study show a significantly reduced risk of short-term sickness absence prior to unit-level downsizing and a significantly increased risk of short-term sickness absence after unit-level downsizing. Similar to our previous study [ 16 ], the results only partially corroborate prior research showing a relationship between organizational change and increased sickness absence and reduced health [ 2 , 57 ], also at the unit-level [ 8 10 ]. Indeed, in line with Østhus and Mastekaasa [ 12 ], our results did not show increased long-term sickness absence at any stage of the downsizing process.…”
Section: Discussionsupporting
confidence: 90%
“…Earlier research has often demonstrated increased sickness absence and reduced health related to both organization-level changes [ 2 , 7 ] and unit-level changes [ 8 10 ]. For example, studies have found a relationship between unit-level structural changes [ 9 ], and organizational-level merger [ 2 ], and increased probability of > 16 days sickness absence [ 2 , 9 ]; between unit-level merger and unit-level layoffs and increased risk of > 28 days absence spells [ 10 ], and between organizational-level downsizing and increased risk of > 3 days absence spells [ 7 ]. However, noteworthy studies have also found limited and even lower odds of long-term sickness absence (> = 15 and > =4 days) in relation to downsizing [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated rates of employee exit (ie, turnover) from the workplace following reorganization have been reported consistently in the literature (7)(8)(9)(10)(11)(12)(13), and studies suggest that organizational changes may have a dual impact on employee exit and health (11,14). Specifically, quarterly employee-exit rates increased from 3.1% to 3.4% after implementation of new healthcare workflows (9), andrelative to no changeexcess employee-exit rates of 15-50% have been demonstrated in the years following merger, splitup, relocation, change of management, and >3 changes performed simultaneously in the healthcare sector (11,12). Such higher employee-exit rates have been associated with adverse psychosocial outcomes among the remaining employees as well as high replacement costs and loss of productivity (15).…”
mentioning
confidence: 78%
“…However, there seems to be a downside to organizational changes in terms of poor employee health and well-being (1)(2)(3)(4)(5)(6). Elevated rates of employee exit (ie, turnover) from the workplace following reorganization have been reported consistently in the literature (7)(8)(9)(10)(11)(12)(13), and studies suggest that organizational changes may have a dual impact on employee exit and health (11,14). Specifically, quarterly employee-exit rates increased from 3.1% to 3.4% after implementation of new healthcare workflows (9), andrelative to no changeexcess employee-exit rates of 15-50% have been demonstrated in the years following merger, splitup, relocation, change of management, and >3 changes performed simultaneously in the healthcare sector (11,12).…”
mentioning
confidence: 99%